Paradoxical effects of Worrisome Thoughts Suppression: the influence of depressive mood - Silva, Sónia (2019)
Thought suppression increases the persistence of unwanted idiosyncratic worries thoughts when individuals try to suppress them. The failure of suppression may contribute to the development and maintenance of emotional disorders. Depressive people seem particulary prone to engage in unsuccessful mental control strategies such as thought suppression. Worry has been reported to be elevated in depressed individuals and a dysphoric mood may also contribute for the failure of suppression. No studies examine, however, the suppression of worisome thoughts in individuals with depressive symptoms. To investigate the suppression effects of worrisome thoughts, 46 participants were selected according to the cut-off score of a depressive symptomatology scale and they were divided in two groups (subclinical and nonclinical group). All the individuals took part in an experimental paradigm of thought suppression. The results of the mixed factorial analysis of variance revealed an increased frequency of worrisome thoughts during the suppression phase on depending of the depressive symptoms. These findings confirm that depressive mood can reduce the success of suppression.